How to Change Epistemological Beliefs? Effects of Scientific Controversies, Epistemological Sensitization, and Critical Thinking Instructions on Epistemological Change - Eric Klopp; Robin Stark (MDPI AG, 2022)
The present study investigates the combination of an epistemological sensitization and two different critical thinking instructions, i.e., the general and infusion approach, in the context of epistemological change induced by the presentation of resolvable scientific controversies. In a randomized study, we tested the hypothesis that the presentation of resolvable controversies generally reduces absolutism and multiplicism and increases evaluativism. We assume that these effects are strongest when the controversies are presented with an epistemological sensitization and the infusion approach. The results indicate an increase in absolutism when the general approach is employed without an epistemological sensitization. Combined with an epistemological sensitization, the increase in absolutism is only detected when the infusion approach is used. Concerning multiplicism, there is a reduction in all conditions, but the reduction is more effective without an epistemological sensitization. The general approach yields a larger increase in evaluativism without an epistemological sensitization, while the infusion approach fosters evaluativism only in combination with the sensitization. However, an argumentation task revealed that the desired level of an evaluativist argumentation only seems to emerge without an epistemological sensitization in combination with the infusion approach. In sum, the results show that there is no general way to reduce absolutism and multiplicism and increase evaluativism.